Cardiovascular risk factors and clinical pattern in young Nepalese population with acute coronary syndrome presenting to a tertiary care center of Nepal - Ravi Sahi; Rajesh Shah; Ratna Mani Gajurel; Raja Ram Khanal; Chandra Mani Poudel; Surya Pathak; Vijay Yadav (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Background and objectives: Cardiovascular disease is a major health problem reaching epidemic proportions. Although Acute Coronary Syndrome (ACS) is an uncommon entity in the young, it constitutes a rising burden in the socioeconomic status of the country because of its impact on the economically productive age group. Early identification and control of the cardiovascular risk factors helps to prevent cases of Myocardial Infarction (MI) in young resulting in reduced health burden. Therefore, we aimed to assess clinical pattern and the prevalence of cardiovascular risk factors in the young and economically productive population of an underdeveloped country to lower the socioeconomic burden. Methods: A total of 60 patients presenting at the cardiology department of Manmohan Cardiothoracic Vascular and Transplant Center were included in our study after fulfilling the inclusion criteria. ACS was diagnosed by cardiac enzymes, electrocardiography, and echocardiography and coronary intervention was done in the cardiac catheterization room. Patients were followed up at 1 and 3-months and reassessed clinically and by echocardiography. Results: Mean age of presentation was 38.55 + 4.98 (SD) years. Over three-fourth of the patients were male (80%) and nearly three-quarter experienced ST-elevated MI (73%). Smoking was the most prevalent risk factor (67%), followed by dyslipidemia (40%), diabetes (32%), hypertension (30%), and obesity (13%). Most of the patients presented with single-vessel disease (65%), followed by double-vessel disease (18%), triple-vessel disease (12%), left main disease (3%), and minor coronary artery disease (2%).  Conclusions: ACS in underdeveloped country is more common in male and single-vessel disease is the most common clinical pattern of ACS and smoking the most prevalent risk factor.